HUBUNGAN INTENSITAS BERMAIN GAME ONLINE MOBILE LEGENDS TERHADAP PERILAKU AGRESIVITAS REMAJA DI KOTA DENPASAR - Kumala, Diyas Putri; Pradipta, Ade Devia; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2024)
ABSTRACT Mobile Legends is an action genre game with a Multiplayer Online Battle Arena (MOBA) system. Mobile Legends is one of the popular games that can cause addiction which leads to aggressive behavior. Aggressive behavior is often carried out in the form of physical aggression and verbal aggression such as hitting, yelling, and berating. The intensity of playing the Mobile Legends game is a measure of the frequency or number of units of time (duration) used in playing. Aggressive behavior as a form of adolescent response to exposure to violent scenes has four aspects, namely physical aggression, verbal aggression, anger, and hostility. This study applied a causal associative research method with a quantitative approach to the theory of media exposure and aggressive behavior. The findings of this study showed that Ha is accepted so that there is a significant correlation between the intensity of playing Mobile Legends games and adolescent aggressive behavior which is moderate and unidirectional. The effect of the intensity of playing Mobile Legends games on adolescent aggressive behavior is 40.8% with a correlation coefficient value of 0.408. A unidirectional relationship describes a positive relationship where an increase in the intensity of playing Mobile Legends games will result in an increase in adolescent aggressive behavior. Conversely, a reduction in the intensity of playing Mobile Legends games will result in a corresponding decrease in the level of aggressive behavior exhibited by the respondents . Keywords: Mobile Legends, Intensity, Aggressive Behavior, Adolescent